Expression analysis of fertilization/early embryogenesis-associated genes in Phalaenopsis orchids - Chen, Jhun-Chen (Plant Signal Behav, 2016)
One of the distinct reproductive programs in orchid species is pollination-triggered ovule development and megasporogenesis. During sexual reproduction, fertilization occurs days to months after pollination. The molecular mechanisms evolved to carry out this strategic reproductive program remain unclear. In the August issue of Plant Physiology(1), we report comprehensive studies of comparative genome-wide gene expression in various reproductive tissues and the molecular events associated with developmental transitions unique to sexual reproduction of Phalaenopsis aphrodite. Transcriptional factors and signaling components whose expression is specifically enriched in interior ovary tissues when fertilization occurs and embryos start to develop have been identified. Here, we report verification of additional fertilization-associated genes, DOMAINS REARRANGED METHYLTRANSFERASE 1 (PaDRM1), CHROMOMETHYLTRANSFERASE 1 (PaCMT1), SU(VAR)3-9 RELATED PROTEIN 1 (PaSUVR1), INDOLE-3-ACETIC ACID inducible 30-like 1 (PaIAA30L1), and ETHYLENE INSENSITIVE 3-like 1 (PaEIN3L1), and discuss their potential roles in gametophyte development, epigenetic reprogramming, and hormone regulation during fertilization and establishment of embryo development in Phalaenopsis orchids.